2008
DOI: 10.1007/s12221-008-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hydrophilicity of poly(trimethylene 2,6-naphthalate)/poly(ethylene glycol) copolymers

Abstract: Poly(trimethylene 2,6-naphthalate) (PTN)/poly(ethylene glycol) (PEG) copolymers were synthesized by the twostep melt copolymerization process of dimethyl-2,6-naphthalenedicarboxylate (2,6-NDC) with 1,3-propanediol (PD) and PEG. The copolymers produced had different PEG molecular weights and contents. The structure, thermal property, and hydrophilicity of these copolymers were studied by proton nuclear magnetic resonance ( 1 H-NMR) analysis, differential scanning calorimetry (DSC), thermogravimetric analysis (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is well known that the surfaces grafted with PS are typically hydrophobic, 55 whereas PEG-coated surfaces are relatively hydrophilic. 56,57 To further confirm the surface composition of the bundled nanofibers, the casting film of SEW-2 obtained from the THF/methanol mixture was further characterized by water wetting. The resulting static contact angle of water was determined to be 125°, indicative of a highly hydrophobic Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the surfaces grafted with PS are typically hydrophobic, 55 whereas PEG-coated surfaces are relatively hydrophilic. 56,57 To further confirm the surface composition of the bundled nanofibers, the casting film of SEW-2 obtained from the THF/methanol mixture was further characterized by water wetting. The resulting static contact angle of water was determined to be 125°, indicative of a highly hydrophobic Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, this smaller value (70°) was in the range of water contact angles on the thin films that were grafted with PEG chains (35-75°). 56,57 These collective data indicated that the regular vesicles were comprised of PS 57 cores and [α-SiW 12 O 40 ] 4− /PEG 45 coronas (Fig. 5).…”
Section: Self-assembly Of Sew-3-5 Yielded Normal Vesicles In Chloroform/methanol Mixture Solventsmentioning
confidence: 87%
“…The instantaneous elastic recovery (IER, %) of samples after the first and the fifth stretch‐recovery cycle was calculated with eq. , and the results were reported as averaged values of five tests of each sample IER=()1normalΔL/L0×100% where L 0 is the original length of the film tested and Δ L is the increase of the film length after the first or the fifth stretch‐recovery cycles.…”
Section: Methodsmentioning
confidence: 99%